Logic and computer design fumdamentals - Mano, M. Morris, 1927-; Kime, Charles R.; Martin, Tom, 1969- (2016)
"For these Global Editions, the editorial team at Pearson has collaborated with educators across the world to address a wide range of subjects and requirements, equipping students with the best possible learning tools. This Global Edition preserves the cutting-edge approach and pedagogy of the original, but also features alterations, customization, and adaptation from the North American version."